Effect of Arachis pintoi on weed control associated with plantain (Musa AAB), Cardenas, Tabasco, Mexico. - Ramos-Hernández, Eder (2011)
The experiment was carried out in Cárdenas, Tabasco,Mexico, in a soil with loamy texture, pH moderately acidic,low content of organic matter and total nitrogen, and cultivated with plantain. The objective was to evaluate the effect of Arachis pintoi as a cover crop for weed controlin plantain crops. The experimental design was factorial, housed in a randomized complete block, with shading and type of plantain plant cover as associated factors. Three replications were used (October 2008-August 2009). Both,the shading and the cover factors had two levels: 50 (s=±13,2) and 45 %(s= ± 11.1), and the ground was covered by weeds and by A. pintoi respectively. Shannon-Wiever (H´)and Sörensen (S) indexes were used to determine species richness. Eleven months after the establishment of theexperiment, H´ values did not differ significantly, S=0.8, inboth shade percentages. The most common weed specieswere T. triangulare, S. podophylum, P. paniculatum and C.diffusa. The treatment with weeds and 50% of shade had statically the highest value of MS (375.3 ± 83.3 g/m2). MS produced by A. pintoi was statically higher (p=0,05) under 45% (198 g/m2) than under 50% shadea (150,4 g/m2). The effectiveness of A. pintoi in weed control was 52.3% under 45% shade, and 70.5% under 50% shade, respectively.